9p-10=10p

Simple and best practice solution for 9p-10=10p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p-10=10p equation:


Simplifying
9p + -10 = 10p

Reorder the terms:
-10 + 9p = 10p

Solving
-10 + 9p = 10p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-10p' to each side of the equation.
-10 + 9p + -10p = 10p + -10p

Combine like terms: 9p + -10p = -1p
-10 + -1p = 10p + -10p

Combine like terms: 10p + -10p = 0
-10 + -1p = 0

Add '10' to each side of the equation.
-10 + 10 + -1p = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -1p = 0 + 10
-1p = 0 + 10

Combine like terms: 0 + 10 = 10
-1p = 10

Divide each side by '-1'.
p = -10

Simplifying
p = -10

See similar equations:

| 9-(5a+2)=-a+5 | | 8x^2-6x^2+7x=0 | | -6-3b=-4b | | 4cos^2x=5sinx-2 | | 9-4(4x-3)=3 | | 7x+5x=0 | | 4x^2+8x^2=0 | | 13+d-27=-3 | | 6(3x+6)=-3x-5(1+4x) | | 7/2=1/9x+26/9 | | 4x^2+3x^2-2x=0 | | 2=X+3x^2 | | -3(7n+4)=-2n+26 | | F(19)=4x+7 | | 256=(-4)x | | 0=-10k+5k | | x=-2+8 | | 5x+2(x+4)=5(2x+10) | | 3(-6-7b)=4(-5b-6) | | 11x+53=7x+55 | | -3-c-6=-3c-6 | | 0.02x-1=2.50 | | x+-10=2y | | -4(2x-3)=-4+6(x-4) | | 2(2r-1)=4r+10 | | 4v^5=4v^3 | | 25x-75=4x-4 | | -7(6x-5)=-42x-35 | | 7(12+x)=7x+84 | | 7(x+2)-2(2x+1)=27 | | 8x+100=9-5x | | 8x-x^2+12=0 |

Equations solver categories